Knowledge management and business strategies theoretical frameworks and empirical research - Abou-Zeid, El-Sayed (Gale virtual reference library, 2008)
"This book provides researchers and practitioners fundamental business and management knowledge by exploring relevant theoretical frameworks and the latest empirical research findings in the area of knowledge and knowledge management strategies and their formulation and alignment with organizations? competitive business strategies"--Provided by publisher.